Comparative Evaluation of Waste Cooking Oil and Waste Engine Oil Rejuvenated Asphalt Concrete Mixtures - Abdullah Al Mamun (14152077) (2022)
In road construction, different types of waste oil have been recommended to overcome the stiffening effect of reclaimed asphalt pavement content. However, the selection of an effective rejuvenator based on a comparative study can lead to using the resources more efficiently. In this study, waste cooking oil and waste engine oil are used to rejuvenate three different percentages (30%, 40%, and 50%) of reclaimed asphalt pavement following the current maximum industrial adaptability. The waste oil rejuvenated mixtures are compared to the fresh mixture, and mixtures rejuvenated with commercial rejuvenator. The moisture sensitivity, indirect tensile strength, and resilient modulus of the various asphalt mixtures are analyzed. Based on the statistical analyses and overall ranking, it is concluded that 7% of waste engine oil performs better till 40% of reclaimed asphalt pavement, whereas 13% of waste cooking oil can be used till 50% of reclaimed asphalt pavement. Other Information Published in: Arabian Journal for Science and Engineering License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s13369-020-04523-5